Does teaching load affect faculty size? - William E. Becker; William H. Greene; John J. Siegfried (Institute for the Study of Labor (IZA), 2009)
Random effects estimates using panel data for 42 colleges and universities over 16 years reveal that the economics faculty size of universities offering a Ph.D. in economics is determined primarily by the long-run average number of Ph.D. degrees awarded annually; the number of full-time faculty increases at almost a one-for-one pace as the average number of Ph.D.s grows. Faculty size at Ph.D. granting universities is largely unresponsive to changes in the number of undergraduate economics degrees awarded at those institutions. In contrast, faculty size at colleges where a bachelor's is the highest degree awarded is responsive to the average number of economics degrees awarded annually, growing by about one for each additional eleven graduating economics majors.
urn:nbn:de:101:1-20090304668
Keywords: A22; A23; C23; J21; 330; Faculty size; student body; Ph.D. degrees; bachelor degrees; Wirtschaftshochschule; Betriebsgröße; Wirtschaftsstudium; Wirtschaftswissenschaftler; USA